Genome-wide association study of Striga resistance in early maturing white tropical maize inbred lines - Adewale, Samuel A.; Badu-Apraku, Baffour; Akinwale, R.O.; Agre, A.P.; Gedil, Melaku A; Garcia-Oliveira, A.L. (Springer, 2020)
Background: Striga hermonthica (Benth.) parasitism militates against increased maize production and productivity in savannas of sub-Saharan Africa (SSA). Identification of Striga resistance genes is important in developing genotypes with durable resistance. So far, there is only one report on the existence of QTL for Striga resistance on chromosome 6 of maize. The objective of this study was to identify genomic regions significantly associated with grain yield and other agronomic traits under artificial Striga field infestation. A panel of 132 early-maturing maize inbreds were phenotyped for key agronomic traits under Striga-infested and Striga-free conditions. The inbred lines were also genotyped using 47,440 DArTseq markers from which 7224 markers were retained for population structure analysis and genome-wide association study (GWAS).